Thermal maturity and gas generation in Upper Cretaceous formations of the Beni Suef Basin, Egypt: insights from stable carbon isotopes and geochemical analysis of the Azhar-E1X well - Farouk, Sherif; Ahmed Saada, Saada; Arafat, Mohamed; Al-Kahtany, Khaled; Gentzis, Thomas; Zaky, Amr S.; Jovane, Luigi (Frontiers in Earth Science, 2025)
This study investigates the origin and thermal maturity of natural gases in Upper Cretaceous reservoirs within the Azhar-E1X well, Beni Suef Basin, Egypt, using stable carbon isotopic analyses of headspace gas samples. Gas shows within the Cretaceous succession, specifically the Bahariya Formation and the Abu Roash “F” Member (A/R “F” Member), were characterized. A total of 15 headspace gas samples and five mud gas samples were analyzed for molecular composition and stable carbon isotopic values (δ13C1, δ13C2, δ13C3). Methane concentrations ranged from 69 to 1,446 ppm in headspace samples and 961–5,670 ppm in mud gases. Isotopic analysis suggests that gases from the A/R “E, F, and G″ members are primarily derived from the primary cracking of kerogen. In contrast, gases from the underlying Bahariya Formation indicate a mixed origin, resulting from both primary cracking of coal-rich kerogen and secondary cracking of oil. The natural gases analyzed are predominantly thermogenic. A normal carbon isotope trend (δ13C1 < δ13C2 < δ13C3) was observed in the headspace gas samples, where methane isotopic compositions are lower than those of ethane.